Studi Karakteristik Bobot Lahir Hasil Persilangan Belgian Blue dan Peranakan Ongole di Provinsi Jawa Barat - Hairul Anwar; Johar Arifin; Primiani Edianingsih (Jurnal Produksi Ternak Terapan, 2023)
Research on birth weight characteristics of crosses of Belgian Blue and Ongole Crossbreeds in West Java was carried out in April – Mei 2022 located in West Java. The purpose of the study was to determine the location of the distribution of Belgian Blue and birth weight characteristics of crosses of Belgian Blue and Ongole Crossbreeds in West Java. The sample used was 17 calves. The method in the research used is exploratory descriptive analysis. The average birth weight of crosses of Belgian Blue and Ongole Crossbreeds is 31,47 ± 6,11 kilograms, with average birth weight of male calves is 30,94 ± 7,88 kilograms and average birth weight of female calves is 31,71 ± 5,56 kilograms. The results of analysis show that the average birth weight of crosses of Belgian Blue and Ongole Crossbreed is higher than the average birth weight of Ongole Crossbreed and lower than the average birth weight of Belgian Blue.